Climate change mitigation: qualitative analysis of environmental impact-reducing strategies in German primary care - Fehrer, Valeska; Poß-Doering, Regina; Weis, Aline; Wensing, Michel; Szecsenyi, Joachim; Litke, Nicola (European journal of general practice, 2023)
BACKGROUND: The German healthcare system is responsible for 5,2% of the national emissions of greenhouse gases. Therefore, mitigation actions to reduce the carbon footprint are crucial. However, there have been few approaches to achieve this in German primary care. OBJECTIVES: This study aimed to identify environmental impact-reducing strategies of German primary care practices. METHODS: During the summer of 2021, a qualitative study was conducted using interviews and focus groups with experts in primary care across Germany, such as physicians, medical assistants, health scientists and experts on the health system level. Verbatim transcribed data were analyzed using Thematic Analysis. RESULTS: The sample comprised 26 individual interviews and two focus groups with a total of N = 40 participants. Findings provide a first overview of pursued mitigation strategies and contextual factors influencing their implementation. Strategies referred to the use of water and energy, recycling and waste management, supply chains and procurement, digitisation, mobility, patient care, behavioural changes and system level. Implementing sustainable actions in daily care was considered expensive and often unfeasible due to lack of staff, time and restrictive hygiene regulations. Participants called for more instruction on implementing mitigating actions, for example, through websites, podcasts, guidelines or quality indicators. CONCLUSION: This study's findings can support the development of future environmental impact-reducing strategies in primary care. Potential options for guidance and support should be considered to facilitate sustainability.
Gesehen am 27.09.2023